Analysis of flow characteristics in sewerage systems - Yap, Hiew Thong (2015)
The resolution of flow characteristics is imperative to all sewerage systems. Design of sewerage system is related to the analysis of flow characteristics. Sewerage system should be designed based on the most critical flow rate. Sewerage system design may become inappropriate if the analysis of flow characteristics is not done. The purpose of this research is to verify the suitable design criterion and by extension parameters for sewerage system as recommended in MS 1228:1991. This research also aims to study the effect of rainfall on sewerage flow pattern and analyze the flow characteristics in sewerage system. In the present study, two parameters, the per capita flow and the design criterion, were investigated. The investigation was performed on a manhole located between the library and sports complex within Universiti Malaysia Pahang, Gambang campus (UMP Gambang) where field monitoring of sewage flows was conducted. ISCO 2150 Area-Velocity Flowmeter was used to collect the flow data and Flowlink 5.1 software was used for data retrieval as well as display. Calibration of the flowmeter was done in the Hydraulics and Hydrology Laboratory of UMP Gambang. The study duration was from 17 November 2014, 4.00 pm to 9 February 2015, 4.00pm. Each set of data consists of sewage flow readings every five minutes for duration of two weeks by using Area-Velocity method. The same data measurement interval was applied to the rainfall data, collected through an ISCO 675 Rain Gauge located at Residential College 2, UMP Gambang. From the results obtained, both the parameters investigated were found to be lower than their respective values stated in the Malaysia Standard MS 1228:1991. The value of average actual per capital flow in this research was 0.076 m3/day/person which is 66.2% smaller than per capita flow in MS 1228:1991 with amount of 0.225 m3/day/person. On the other hand, the value of average actual design criterion in this study was 2.49 also smaller than design criterion of 4.7 mentioned in MS 1228:1991. After analysis of the results, it can be concluded that the flow characteristics in the sewerage system studied is sufficient to cater to the population equivalent in the study.